Penerapan MIT Inventor Dalam Pemasaran Produk Honda Arista Bengkulu Menggunakan Aplikasi Android - Khairullah Khairullah; Ujang Juhardi; Indra Yoga Widianto (UNIVED Press, 2024)
The main objective of this thesis is to design an Android application specifically developed for the Honda Arista dealership in Bengkulu, using the MIT App Inventor platform. This application is designed to provide easy access for customers, allowing them to obtain information related to Honda products, after-sales services, and providing facilities for service appointment reservations. To achieve this goal, the research will adopt a development method using code block programming in MIT App Inventor. During the implementation process, the author will focus on an intuitive user interface design, ensuring compatibility with various Android devices, and integrating features that meet the needs of the Honda Arista dealership and its customers. The importance of creating an application that can be easily accessed by users without a conventional programming background is a primary concern. Therefore, this research will prioritize the use of visual programming provided by MIT Inventor, enabling application development without requiring in-depth programming knowledge. The expected outcome of this research is the development of an Android application that can be used by Honda Arista customers in Bengkulu. This application will not only provide ease of access to product information and service appointments but also enable customers to make reservations easily through the platform. In addition to benefiting customers, this application is expected to enhance the quality of dealership services, increase operational efficiency, and create better interaction with consumers. Through the implementation of this Android application, it is hoped that Honda Arista Bengkulu customers will experience more comfortable and efficient interactions. Additionally, the Honda Arista dealership is expected to leverage this technology to enhance brand image, expand market reach, and gain more advantages in an increasingly competitive business environment